Student negotiation of an undergraduate accounting assessment - Hyland, Tarryn (School of Education, 2017)
In South Africa (SA), access to the accounting profession is characterised by inequality, resulting from a multitude of socio-economic and historical issues. Assessment serves as the primary gate-keeping mechanism of the profession. However, more than twenty years after the end of apartheid, pass rates remain skewed by factors such as language and race. Accounting education research offers some quantitative studies which investigate diversity in academic performance by school-leaving results or by race, for example, and a number of studies which consider language in the accounting curriculum. The quantitative studies, however, do not provide insight into the complex socio-cultural issues operating in accounting education, and the work on language in accounting education is largely focused on action research projects and the documentation of communication interventions. While some accounting education studies acknowledge that specific disciplinary conventions exist, these practices are not analysed or described. This study asks the question: how do students negotiate undergraduate accounting assessments? To explore this problem, the academic communication practices in a second-year accounting assessment at a wellestablished, English-medium university in SA are investigated by analysing what is valued in accounting assessments, what students are doing in the assessment event, and why. Academic literacies research and a theory of language as social practice, including the work of Theresa Lillis and Norman Fairclough, are used to develop the theoretical framework of this study. Critical discourse analysis (CDA) is used to analyse the assessment texts, explore the dominant disciplinary practices in accounting higher education and explain the power behind professional accounting education discourse. This study outlines elements of the valued disciplinary literacy, such as the genres of accounting assessments and the accounting discussion answer, and specialised test-taking reading practices, including how to identify the valued task response. The overarching feature of the dominant disciplinary practices is its linguistic complexity, largely shaped by professional accounting institutions. To investigate students' literacy practices, the answer texts of three students from different backgrounds are analysed using CDA, together with ethnographic data from "talk around text" (Lillis, 2008: 355) and "literacy history" (Lillis, 2008: 362) interviews with students. This study shows that students with language practices aligned to the valued professional education discourse have power in the assessment, while English additional language students from poorer schooling backgrounds in particular struggle to grasp and demonstrate the valued discourse. This study contributes to research on language practices and student experiences in a professional curriculum. It is my hope that the insights offered by this paper can be used to improve teaching and learning by encouraging educators to be aware of, and facilitate access to, the dominant accounting disciplinary practices. Educators need to acknowledge the diverse language practices of students, make explicit the complex elements of the valued disciplinary practices in the teaching and provide opportunities to develop students' knowledge of business and legal concepts, for example, which are recontextualised in the accounting curriculum. Until these steps are taken to make the epistemology of the discipline clearer, access to the accounting profession will remain unequal.